2022
DOI: 10.1038/s41419-022-05001-6
|View full text |Cite
|
Sign up to set email alerts
|

Mid1 is associated with androgen-dependent axonal vulnerability of motor neurons in spinal and bulbar muscular atrophy

Abstract: Spinal and bulbar muscular atrophy (SBMA) is an adult-onset hereditary neurodegenerative disease caused by the expansions of CAG repeats in the androgen receptor (AR) gene. Androgen-dependent nuclear accumulation of pathogenic AR protein causes degeneration of lower motor neurons, leading to progressive muscle weakness and atrophy. While the successful induction of SBMA-like pathology has been achieved in mouse models, mechanisms underlying motor neuron vulnerability remain unclear. In the present study, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…We first showed that DHT treatment inhibited neurite outgrowth in the presence of polyQ-expanded AR, independent of its transcriptional ability at AREs, while hormone had no effect on neurite outgrowth in the presence of wild-type AR. The inhibition of polyQ-expanded AR on neurite outgrowth is consistent with previous findings of reduced axonogenesis in spinal cord slice cultures from SBMA mice ( 50 ). The lack of growth-enhancing effect of DHT in the presence of normal polyQ-length AR, however, seemingly contradicts prior studies ( 24 , 25 , 51 , 52 ).…”
Section: Discussionsupporting
confidence: 91%
“…We first showed that DHT treatment inhibited neurite outgrowth in the presence of polyQ-expanded AR, independent of its transcriptional ability at AREs, while hormone had no effect on neurite outgrowth in the presence of wild-type AR. The inhibition of polyQ-expanded AR on neurite outgrowth is consistent with previous findings of reduced axonogenesis in spinal cord slice cultures from SBMA mice ( 50 ). The lack of growth-enhancing effect of DHT in the presence of normal polyQ-length AR, however, seemingly contradicts prior studies ( 24 , 25 , 51 , 52 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previously published microarray data on Gene Expression Omnibus, GSE39865 25 , was normalized using Robust Multichip Analysis of Bioconductor based on R (https://www.rproject.org), as previously described 15 . The resultant data was subjected to the GAGE analysis and WGCNA using iDEP.96 (http://bioinformatics.sdstate.edu/idep96/) 54 .…”
Section: Analysis Of Microarray Datamentioning
confidence: 99%
“…These studies suggest that polyQ-expanded AR induces transcriptional dysregulation in the early developmental stage. Recently, we have addressed impaired axonal outgrowth of motor neurons in the slice culture of embryonic spinal cord of a transgenic mouse model (AR-97Q) 15 , suggesting the neurotoxicity due to early androgen exposure during developmental stages. These findings prompted us to further investigate the effects of polyQ-expanded AR at the very early, preclinical stage in SBMA, in consideration of the following facts: first, circulating testosterone levels transiently increase immediately after birth to the similar levels in adulthood in rodents and human 16,17 ; second, this neonatal testosterone surge coincides with neurodevelopment events including synaptogenesis, gliogenesis, and synaptic pruning 18 , which determines morphological and physiological properties of motor neurons 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Loss-of-function mutations of Mid1 cause Opitz G/BBB syndrome in humans. Additionally, it has been reported to have involvement in the pathology of asthma, cancer, and neurodegenerative diseases [18][19][20]. However, its implication in autoimmune disease has not been extensively studied [21,22].…”
Section: Introductionmentioning
confidence: 99%